Material Biokomposit Sebagai Material Alternatif Sungkup Helm - Boy Rollastin (Politeknik Manufaktur Negeri Bangka Belitung, 2017)
A Helmet is an equipment that should be used by motorcycle riders. The correct function of helmets is to protect motorcycle riders from head injuries during accident and head collision. Most of helmets existing in markets are produced by helmet factories. Those helmets have to meet certain standards, including the use of materials to construct the helmet lid and the testing processes on the helmet itself. The price of used materials is quite high because those materials are still imported from overseas. It causes the increasing of helmet production cost and the helmet prices in the market become quite expensive. This research aims to find how a biocomposite material (consisting of 85% PP, 10% rice husk and 5% MAPP) can be used as an alternative replacement material for helmet lid preparation. The process is conducted by using finite element software. The result of the testing shows that the test penetration model with 4 mm thickness is not penetrated by indenters. Whereas the result of impact simulation testing of 146.84 g is still classified as a safe limit in accordance with the requirements of SNI 1811-2007 of 300 g.